Vindkraft och rennäring - Arenius, Johan (2013)
The Swedish Parliament has decided to increase the share of electricity produced by wind power. The same parliament has decided that the Sami have the right to herd reindeer over 50% of the country's land area. In this literature review the potential impact wind power development and associated infrastructure may have on reindeer husbandry conditions are examined. The unique physiology of the reindeer enables it to live out of grazing in the arctic climate in the north of Sweden. For reindeer husbandry to be long-term productive and sustainable, it is important that there is enough land for grazing. The research available on how reindeer are disturbed by human activities such as roads, mines, hikers, etc., clearly indicates that the reindeer avoids areas close to such disturbance. How sensitive the reindeer are for the disturbance varies over the year. In cases where the reindeers are forced to adapt to disturbance if no other land is available, some habituation has occurred. Similarly, some reduction in flight distance have been recorded when the reindeer regularly have been exposed to disturbance from snowmobiles and hikers. This literature review concludes that the reindeer husbandry is negatively affected when the pastures are exploited for wind power. The two industries have to find ways to coexist where the construction as well as the management of the wind turbines is done in a way that minimizes disturbance to reindeer husbandry. Sveriges riksdag har beslutat att öka andelen el som produceras genom vindkraft. Samma riksdag har beslutat att samerna har rätt att bedriva renskötsel på 50 % av Sveriges yta. I denna litteraturstudie studeras den eventuella påverkan utbyggnad av vindkraft och tillhörande infrastruktur kan ha på rennäringens förutsättningar. Renens unika fysiologi möjliggör för den att tillgodogöra sig det bete som finns tillgängligt i norra Sverige. För att en renhjord skall vara långsiktigt produktiv och hållbar är det viktigt att det finns tillräckligt mycket bete. Den forskning som finns ...